Inconstitucionalidad del artículo 71 de la ley orgánica de educación superior en relación a la inobservancia e inaplicabilidad del principio de igualdad de oportunidades - Rojas Fierro, Pablo Andrés (2023)
The following research work "Unconstitutionality of article 71 of the organic law of higher education in relation to the non-observance and inapplicability of the principle of equal opportunities" a doctrinal analysis of article 71 of the organic law of higher education reveals that it is necessary to implement it, since it does not guarantee equal opportunities for access to higher education and integration of foreigners and people with disabilities into the system. The article claims that the only method of access to higher education is an admission test created by the governing body in this case the SENESCYT (National Secretariat of Higher Education. There is, however, a public interest that higher education is a fundamental right that the State must protect, so the legal aspects of the principle of equal opportunities ignore the rights of the CRE. The way in which students are able to access universities and the opportunities for inclusion without discrimination within the system of accessing higher education need to be changed. Materials and methods were utilized for the development of this legal research, which included conducting interviews and surveys among legal professionals. Consequently, the results were used to propose an amendment to the Organic Law of Higher Education and general regulations to the Organic Law of Higher Education in Article 20, incorporating norms that determine the elaboration of new access methods in relation to the university entrance exams, confirming the rights of study and principles of equality that regulate opportunities for people who are abroad and people with disabilities for their effective guarantee of access to higher education.